2002
DOI: 10.1038/nn950
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal correlates of decision-making in secondary somatosensory cortex

Abstract: The ability to discriminate between two sequential stimuli requires evaluation of current sensory information in reference to stored information. Where and how does this evaluation occur? We trained monkeys to compare two mechanical vibrations applied sequentially to the fingertips and to report which of the two had the higher frequency. We recorded single neurons in secondary somatosensory cortex (S2) while the monkeys performed the task. During the first stimulus period, the firing rate of S2 neurons encoded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
283
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 346 publications
(314 citation statements)
references
References 37 publications
21
283
2
Order By: Relevance
“…Little is known about the neural correlates of haptic sensing but recent work by Romo, Salinas, and colleagues Salinas 2001, 2003;Romo et al 2002) is directly relevant to this question. They studied a task in which monkeys were required to discriminate the frequency of 2 vibratory stimuli presented in succession.…”
Section: T E M P O R a L A S P E C T S O F H A P T I C P E R C E P T mentioning
confidence: 99%
“…Little is known about the neural correlates of haptic sensing but recent work by Romo, Salinas, and colleagues Salinas 2001, 2003;Romo et al 2002) is directly relevant to this question. They studied a task in which monkeys were required to discriminate the frequency of 2 vibratory stimuli presented in succession.…”
Section: T E M P O R a L A S P E C T S O F H A P T I C P E R C E P T mentioning
confidence: 99%
“…We found that the activity of the recorded neurons of several cortical areas encodes f1 in a monotonic firing rate code beginning in the primary somatosensory cortex (5-7), continuing in the secondary somatosensory cortex (5), the ventral premotor cortex (19), the prefrontal cortex (10), and the medial premotor cortex (MPc) (18). Except for the primary somatosensory cortex, these cortical areas encode information of f1 during the delay period between f1 and f2 (5,10,11,(17)(18)(19). During presentation of f2, some neurons of all these cortical areas respond to f2, but some other neurons reflect past information of f1, or of the difference between f2 and f1, and generate a differential response consistent with the decision motor report (17)(18)(19).…”
mentioning
confidence: 99%
“…medial premotor cortex ͉ monkeys ͉ sensory discrimination ͉ working memory S tudies in behaving monkeys that combine psychophysical and neurophysiological experiments have provided new insights into how a neural representation of a sensory stimulus relates to perception (1)(2)(3)(4)(5)(6)(7)(8), memory (9)(10)(11)(12), and decision making (13)(14)(15)(16)(17)(18)(19). In particular, there has been important progress regarding the neural codes associated with these cognitive functions in the visual and somatic modality (20,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although much attention has been given to sensorimotor interaction in SI, there is little evidence of such a phenomenon in the SII and the role of SII in motor execution has not been fully elucidated in humans. Compared with the SI, the SII is speculated to serve a higher level of cognitive function in somatosensory information processing, such as attention, decision-making, object recognition, and the integration of nociceptive and non-nociceptive inputs [60][61][62][63][64] . Our results show that these cortical areas play different roles in the function of sensorimotor integration.…”
Section: Implications From Imaging Studiesmentioning
confidence: 99%